Size Effect on Flexural and Fracture Properties of Polypropylene Fiber-reinforced Engineered Cementitious Composite - Hosseini Mehrab, Alireza; Amirfakhrian, Seyedmahdi; Esfahani, M. Reza (Periodica Polytechnica Civil Engineering, 2023)
The size effect on flexural properties and fracture behavior of polypropylene fiber-reinforced engineered cementitious composite (PPFECC) containing local waste materials was investigated. Geometrically similar notched beams with dimensions of 190 × 70 × 70 mm (small), 380 × 70 × 140 mm (medium), and 760 × 70 × 280 mm (large) were tested using three-point bending to study the size effect on flexural properties, toughness, and fracture behavior in PPFECC and the influence of tensile ductility of PPFECC on the size effect parameter. Two PPFECC mixtures containing 1% (PPFECC1) and 2% (PPFECC2) volume fraction of polypropylene fibers were prepared. The results indicated clear size effect on ductility, flexural strength, normalized deflection, normalized toughness, and fracture energy for both PPFECCs. The flexural properties and fracture behavior in PPFECC1 were more sensitive to the size effect parameter due to its lower tensile ductility compared to PPFECC2. Moreover, according to Bažant’s size effect curve, the behavior of notched beams in PPFECC2 with higher tensile ductility was closer to the strength criterion compared to PPFECC1.